An in vitro model of renal inflammation after ischemic oxidative stress injury: nephroprotective effects of a hyaluronan ester with butyric acid on mesangial cells - Baraldi O (Dove Medical Press, 2017)
Olga Baraldi,1 Francesca Bianchi,2,3 Viola Menghi,1 Andrea Angeletti,1 Anna Laura Croci Chiocchini,1 Maria Cappuccilli,1 Valeria Aiello,1 Giorgia Comai,1 Gaetano La Manna1 1Department of Experimental, Diagnostic and Specialty Medicine, Nephrology, Dialysis and Renal Transplant Unit, Sant’Orsola-Malpighi Hospital, University of Bologna, Bologna, 2Stem Wave Institute for Tissue Healing, Gruppo Villa Maria Care & Research – Ettore Sansavini Health Science Foundation, Lugo, Ravenna, 3National Institute of Biostructures and Biosystems at the Department of Experimental, Diagnostic and Specialty Medicine, Sant’Orsola-Malpighi Hospital, University of Bologna, Bologna, Italy Background: Acute kidney injury, known as a major trigger for organ fibrosis and independent predictor of chronic kidney disease, is characterized by mesangial cell proliferation, inflammation and unbalance between biosynthesis and degradation of extracellular matrix. Therapeutic approaches targeting the inhibition of mesangial cell proliferation and matrix expansion may represent a promising opportunity for the treatment of kidney injury. An ester of hyaluronic acid and butyric acid (HB) has shown vasculogenic and regenerative properties in renal ischemic-damaged tissues, resulting in enhanced function recovery and minor degree of inflammation in vivo. This study evaluated the effect of HB treatment in mesangial cell cultures exposed to H2O2-induced oxidative stress.Materials and methods: Lactate dehydrogenase release and caspase-3 activation were measured using mesangial cells prepared from rat kidneys to assess necrosis and apoptosis. Akt and p38 phosphorylation was analyzed to identify the possible mechanism underlying cell response to HB treatment. The relative expressions of matrix metallopeptidase 9 (MPP-9) and collagen type 1 alpha genes were also analyzed by quantitative real-time polymerase chain reaction. Cell proliferation rate and viability were measured using thiazolyl blue assay and flow cytometry analysis of cell cycle with propidium iodide.Results: HB treatment promoted apoptosis of mesangial cells after H2O2-induced damage, decreased cellular proliferation and activated p38 pathway, increasing expression of its target gene MPP-9.Conclusion: This in vitro model shows that HB treatment seems to redirect mesangial cells toward apoptosis after oxidative damage and to reduce cell proliferation through p38 MAPK pathway activation and upregulation of MPP-9 gene expression involved in mesangial matrix remodeling. Keywords: acute kidney injury, apoptosis, hyaluronan ester of butyric acid, mesangial cells